Fiber concrete and preparation method thereof

By using polyaniline and basalt fibers in concrete, the problem of insufficient mechanical properties and durability of traditional concrete is solved, and higher compression, bending, tensile strength and toughness are achieved, which is suitable for complex engineering needs.

CN119797853APending Publication Date: 2025-04-11CHINA 19TH METALLURGICAL CORP

Patent Information

Application Number
CN202510203765.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Traditional concrete has shortcomings in terms of mechanical properties and durability, low tensile strength, poor toughness, and is susceptible to chemical corrosion and freeze-thaw cycles, making it difficult to meet the needs of complex engineering such as high-rise buildings and large-span bridges.

Method used

Polyaniline and basalt fibers are used as raw materials to prepare fiber concrete through dry mixing and stirring, which improves its compressive, bending, tensile strength and toughness.

Benefits of technology

It significantly improves the comprehensive performance of concrete, enhances crack resistance and durability, reduces maintenance costs, and expands the application range in high-performance building structures, transportation infrastructure and special engineering environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005283930020000071
    Figure BDA0005283930020000071
  • Figure BDA0005283930020000081
    Figure BDA0005283930020000081
  • Figure BDA0005283930020000091
    Figure BDA0005283930020000091
Patent Text Reader

Abstract

The invention belongs to the technical field of concrete preparation, and particularly relates to fiber concrete and a preparation method thereof. In order to improve the mechanical property and durability of concrete, the invention provides fiber concrete, which is prepared from the following raw material components in parts by weight: 400 to 500 parts of cement, 750 to 1800 parts of aggregate, 4 to 8 parts of polyaniline fiber, 10 to 25 parts of basalt fiber and 140 to 180 parts of water. According to the concrete disclosed by the invention, by adding polyaniline and basalt fiber, the comprehensive performance such as compression resistance, bending resistance, tensile strength and toughness of the concrete is remarkably improved, the application range of the concrete in the fields of high-performance building structures, traffic infrastructures, special engineering environments and the like is expanded, the material performance is improved, and efficient utilization of resources is realized; the material consumption is reduced, and the influence on the environment is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete preparation, and in particular relates to fiber concrete and a preparation method thereof. Background Art

[0002] In today's construction and engineering fields, concrete is one of the most widely used basic materials, and its performance improvement and innovation have always attracted much attention. Judging from the dilemma of traditional concrete, although it is widely used, its shortcomings are obvious. In terms of mechanical properties, the tensile strength is only one-tenth of the compressive strength. It is very easy to crack when bent and stretched, and its toughness is poor. It often breaks brittlely when facing impact or dynamic loads. In terms of durability, chemical corrosion such as acid rain and seawater erosion, as well as freeze-thaw cycles, will greatly reduce its lifespan, making it difficult to meet the demand for high-strength and long-life materials such as high-rise buildings and large-span bridges, and also limiting its application in the chemical and marine engineering fields.

[0003] Fiber reinforced concrete technology brings hope for solving these problems. However, in the current fiber concrete research, steel fiber is not corrosion resistant enough; polypropylene fiber strength and elastic modulus are poor, prompting researchers to explore the way to composite fibers with other materials. Among them, patent CN117024719A discloses a liquid crystal polymer, fiber and its preparation method, and fiber concrete. The fiber concrete is prepared by mixing four monomers of p-hydroxybenzoic acid, 6-hydroxybenzofuran-2-carboxylic acid, biphenyl, and isophthalic acid with an acylating agent and a catalyst in a specific ratio to obtain a reaction mixture; the reaction mixture is subjected to a prepolymerization reaction to obtain a prepolymer; in an inert gas atmosphere, the prepolymer is subjected to a solid phase polycondensation reaction to obtain a liquid crystal polymer, which is then combined with fiber and concrete to form a new type of fiber concrete. However, the preparation process of this fiber concrete is relatively complicated and costly, and is not suitable for engineering projects such as bridges in mountainous areas. Summary of the invention

[0004] In order to improve the mechanical properties and durability of concrete, the present invention provides a fiber concrete and a preparation method thereof. The fiber concrete is added with polyaniline and basalt fiber, which can significantly improve the comprehensive properties of concrete such as compression, bending, tensile strength and toughness, expand the application scope of concrete in high-performance building structures, transportation infrastructure and special engineering environments, improve material properties, achieve efficient resource utilization, reduce material consumption, and reduce environmental impact.

[0005] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0006] In a first aspect, the present invention provides a fiber concrete, wherein the raw material components thereof include, by weight: 400-500 parts of cement, 750-1800 parts of aggregate, 4-8 parts of polyaniline fiber, 10-25 parts of basalt fiber and 140-180 parts of water.

[0007] Preferably, the raw material components include: 450 parts of cement, 1650 parts of aggregate, 6 parts of polyaniline fiber, 15 parts of basalt fiber and 160 parts of water.

[0008] Wherein, the cement is silicate cement.

[0009] Preferably, the cement is P·II type silicate cement.

[0010] Wherein, the aggregate is at least one of coarse aggregate or fine aggregate.

[0011] Preferably, the coarse aggregate is continuously graded granite crushed stone with a particle size of 5-25 mm.

[0012] Preferably, the fine aggregate is river sand or machine-made sand, and more preferably, it is medium river sand with a fineness modulus of 2.6-3.0.

[0013] Preferably, the coarse aggregate is 900 parts and the fine aggregate is 750 parts.

[0014] Wherein, the polyaniline fiber has a length of 8-12 mm and a diameter of 20-30 μm.

[0015] Wherein, the basalt fiber has a length of 6-10 mm and a diameter of 10-15 μm.

[0016] Furthermore, the fiber concrete also includes, by weight, 0.5 to 60 parts of additives and 30 to 110 parts of mineral admixtures as raw material components.

[0017] Wherein, the admixture includes at least one of a high-efficiency water reducing agent, a waterproofing agent, a retarder or an expansion agent.

[0018] Preferably, the high-efficiency water reducer is a polycarboxylic acid-based high-efficiency water reducer.

[0019] Preferably, the waterproofing agent is a cement-based penetrating crystalline waterproofing agent.

[0020] Preferably, the retarder is a hydroxycarboxylic acid and its salt retarder.

[0021] Preferably, the expansion agent is a calcium sulphoaluminate expansion agent.

[0022] Most preferably, the admixture includes 15 parts of polycarboxylic acid-based high-efficiency water reducing agent, 8 parts of cement-based penetrating crystalline waterproofing agent, 0.6 parts of hydroxycarboxylic acid and its salt retarder and 30 parts of calcium sulfoaluminate expansion agent.

[0023] Wherein, the mineral admixture is selected from at least one of fly ash or silica fume.

[0024] Preferably, the mineral admixture includes 70 parts of fly ash and 30 parts of silica fume.

[0025] In a second aspect, the present invention provides a method for preparing the above-mentioned fiber concrete, which comprises the following steps:

[0026] First, dry-mix cement and aggregate evenly, then add polyaniline fiber and basalt fiber, continue stirring, and finally add water and stir evenly to obtain fiber concrete.

[0027] Furthermore, cement, aggregate and mineral admixture are first dry-mixed uniformly, and then polyaniline fiber and basalt fiber are added and stirred continuously, and finally water and admixture are added and stirred uniformly to obtain fiber concrete.

[0028] Beneficial effects: The present invention provides a concrete prepared with polyaniline and basalt fiber as raw materials. The concrete has enhanced compression, bending, tensile strength and toughness through the combined action of basalt fiber and polyaniline fiber, and improves the microstructure and durability with the help of polyaniline fiber, so that it can better resist chemical erosion and freeze-thaw cycles. At the same time, due to the high temperature resistance of basalt fiber and the high temperature stability of polyaniline fiber, the fire safety of the prepared concrete is improved, and the application scope of the concrete in high-performance building structures, transportation infrastructure and special engineering environments is expanded, meeting the needs of complex engineering. Moreover, since the prepared concrete has good durability and low maintenance cost, it can achieve efficient resource utilization, reduce material consumption, and reduce environmental impact by improving material performance, thereby promoting sustainable development in the field of building materials. DETAILED DESCRIPTION

[0029] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clear, the present application is further described in detail below in combination with the implementation methods. Unless otherwise defined, all scientific and technological terms used herein have the same meanings as understood by ordinary technicians in the field.

[0030] In one embodiment of the present invention, a fiber concrete is first provided, and its raw material components include, by weight: 400-500 parts of cement, 750-1800 parts of aggregate, 4-8 parts of polyaniline fiber, 10-25 parts of basalt fiber and 140-180 parts of water.

[0031] In a further embodiment of the present invention, the fiber concrete further comprises, by weight, 0.5 to 60 parts of admixtures and 30 to 110 parts of mineral admixtures as raw material components.

[0032] The various raw material components of the above-mentioned fiber concrete play the following roles respectively:

[0033] cement:

[0034] Cement is the main cementitious material of concrete and plays a key role in fiber concrete.

[0035] In a specific embodiment of the present invention, the cement used is silicate cement, which has the characteristics of high early strength and can provide good initial mechanical properties for concrete, so that the concrete can obtain sufficient strength to bear the load in a relatively short time.

[0036] In the preferred embodiment of the present invention, P·II type silicate cement is used. This cement has the characteristics of high early strength and strong corrosion resistance, which is beneficial to improving the compressive strength and durability of concrete and is suitable for important structural projects such as bridges.

[0037] Aggregates:

[0038] In one specific embodiment of the present invention, the aggregate is at least one of coarse aggregate or fine aggregate.

[0039] The coarse aggregate is crushed stone, preferably granite crushed stone with a particle size of 5-25mm and continuous gradation. The coarse aggregate forms the skeleton of the concrete and bears the main pressure load. The continuously graded crushed stone can make the skeleton structure more stable and improve the compressive strength.

[0040] Fine aggregate is river sand or machine-made sand, and medium river sand with a fineness modulus of 2.6-3.0 is preferred. Sand fills the gaps in the coarse aggregate to make the concrete more compact, and a good fineness modulus ensures the workability of the concrete.

[0041] Polyaniline fiber:

[0042] Polyaniline fibers preferably have a length of 8-12 mm and a diameter of 20-30 μm. Such fibers can effectively prevent the expansion of cracks in concrete, bridge cracks, and enhance the crack resistance of concrete. Its conductive properties can also be used to monitor changes in the internal structure of concrete.

[0043] Basalt Fiber:

[0044] Basalt fiber has high strength and modulus, with a tensile strength of 3000-4840MPa, an elastic modulus of 93-110GPa, and a melting point of 1450-1500°C. Basalt fiber has high strength and modulus, and can work with polyaniline fiber to further enhance the toughness and crack resistance of concrete. The present invention preferably selects basalt fiber with a length of 6-10mm and a diameter of 10-15μm.

[0045] In the present invention, polyaniline and basalt fiber work together to significantly improve the mechanical properties of concrete:

[0046] Enhanced compressive strength: Basalt fibers form a three-dimensional randomly distributed support system inside the concrete. When the concrete is under pressure, the fibers can effectively share the pressure and prevent the expansion and connection of microcracks.

[0047] Improved flexural properties: The combined effect of polyaniline and basalt fiber significantly improves the flexural strength of concrete. The high elastic modulus and good tensile properties of basalt fiber can provide tensile force when concrete is bent, just like setting many tiny "rebars" inside the concrete. At the same time, polyaniline fiber improves the microstructure inside the concrete, making the bond between the cement matrix and the fiber stronger.

[0048] Excellent crack resistance: Basalt fiber can inhibit the early plastic shrinkage cracks and drying shrinkage cracks of concrete. In the early stage of concrete hardening, the fiber can restrain the deformation of the matrix and reduce shrinkage cracks caused by water evaporation and other reasons. Polyaniline can also further improve the toughness of concrete through its special chemical structure and physical properties, so that the concrete can consume energy through its own deformation when subjected to external forces, thereby delaying the appearance and expansion of cracks.

[0049] In the present invention, the combined effect of polyaniline and basalt fiber can also significantly improve the durability of concrete:

[0050] Enhanced chemical corrosion resistance: Polyaniline has a certain chemical stability and can resist corrosion from acid, alkali, salt and other chemical substances in concrete. For some concrete structures in chemical environments or coastal areas, such as the floor of chemical plants and seaside breakwaters, polyaniline and basalt fiber concrete can effectively prevent chemical substances from corroding concrete and extend the service life of the structure.

[0051] Improved freeze-thaw resistance: The addition of basalt fiber can improve the pore structure of concrete and reduce the number of harmful pores. Polyaniline can reduce the expansion and contraction stress of concrete during freeze-thaw cycles. In roads, bridges and other projects in cold areas, after multiple freeze-thaw cycles, the mass loss rate and strength loss rate of concrete are significantly lower than those of ordinary concrete.

[0052] Moreover, concrete made of polyaniline and basalt fiber has good durability, and the number and degree of maintenance required during its service life are greatly reduced. The high performance of this concrete can reduce the cross-sectional size of the structure in some projects and reduce the overall material consumption.

[0053] At the same time, basalt fiber itself has good high temperature resistance. In the event of a fire, this fiber can prevent the rapid collapse of the concrete structure to a certain extent, providing more time for personnel evacuation and fire rescue. Polyaniline also has a certain stability at high temperatures, which helps to improve the fire resistance of concrete structures and reduce the degree of damage caused by fire to buildings.

[0054] water:

[0055] Water is mainly used for hydration reaction with cement in concrete. A suitable water-cement ratio (mass ratio of water to cement) is crucial to the performance of concrete. Through preliminary screening, the applicant found that the optimal water-cement ratio is 400-500 parts of cement and 140-180 parts of water. 450 parts of cement and 160 parts of water are preferred.

[0056] Admixtures:

[0057] In order to improve the working properties and other properties of concrete, admixtures are also added, such as high-efficiency water reducers, waterproofing agents, retarders or expansion agents.

[0058] Among them, the high-efficiency water reducer can reduce the water consumption under the premise of ensuring the workability of concrete, thereby reducing the porosity of concrete, while improving the fluidity of concrete, and improving strength and durability. In one embodiment of the present invention, a polycarboxylic acid-based high-efficiency water reducer is preferred, which also has good slump retention performance and is beneficial to the construction of concrete.

[0059] Among them, in rainy areas, waterproofing agents are the key to improving the durability of concrete. Waterproofing agents can fill the pores of concrete, prevent the intrusion of water, and prevent the corrosion of steel bars and the erosion of concrete. In one embodiment of the present invention, a cement-based penetrating crystalline waterproofing agent is preferred, which, under the guidance of water, penetrates into the internal pores and microcracks of concrete to form insoluble and stable crystals. When the crack width is ≤0.5mm, it can be automatically repaired by secondary crystallization when exposed to water, and the waterproof effect is long-lasting. It has been tested that it can withstand a water pressure of more than 1.5MPa. Dense concrete structure, effectively blocking CO 2 , Cl - It can also slow down the corrosion of steel bars and carbonization of concrete, greatly improving the durability of the structure and extending its service life.

[0060] Among them, the retarder can prolong the setting time of concrete, facilitate construction under high temperature environment, and at the same time make the hydration heat release of concrete more uniform, reducing the generation of temperature cracks. In one embodiment of the present invention, hydroxycarboxylic acid and its salt retarder are preferred, which form complexes with calcium ions on the surface of cement particles, accurately delay the hydration reaction process of cement, effectively prolong the initial setting and final setting time of concrete, and ensure that concrete has sufficient operating time under complex construction conditions. In the retarding process, the cement stone structure is optimized to make the transition zone between cement stone and fiber interface more dense, enhance the bonding force between the two, thereby improving the later strength of concrete and enhancing crack resistance.

[0061] Among them, the expansion agent can compensate for the shrinkage of concrete, produce a certain expansion during the hardening process of concrete, reduce the occurrence of shrinkage cracks, and improve the crack resistance and compactness of concrete. In one embodiment of the present invention, calcium sulfoaluminate expansion agent is preferred, which reacts with gypsum and calcium hydroxide in cement paste to generate calcium aluminate and produce moderate expansion. Compensate for the shrinkage deformation of concrete during the hardening process, offset the shrinkage stress caused by temperature changes and water loss, reduce the occurrence of cracks from the root, and improve the crack resistance of the structure. Strengthen the bond strength between the fiber and the cement matrix, give full play to the fiber bridging crack resistance effect, and further improve the crack resistance and tensile resistance of concrete.

[0062] Mineral admixture: The mineral admixture is selected from at least one of fly ash or silica fume.

[0063] Among them, fly ash can improve the workability of concrete, reduce hydration heat, and reduce the occurrence of temperature cracks inside concrete. At the same time, it can also undergo secondary hydration reaction with cement hydration products to improve the later strength and durability of concrete.

[0064] Among them, silica fume particles are extremely fine and can fill the gaps between cement particles, making the concrete more compact, improving the strength and impermeability of the concrete, and enhancing the durability of the concrete in rainy environments.

[0065] Specific examples will be listed below to explain the scheme of the present invention. It will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the examples, the techniques or conditions described in the literature in this area or the product instructions are used. Reagents or instruments used that do not indicate manufacturers are all conventional products that can be obtained commercially.

[0066] Example 1 Preparation of fiber concrete

[0067] 1. Raw material preparation and mixing

[0068] The raw materials shown in Table 1 are weighed according to the weight ratio, and the cement and the aggregates and mineral admixtures shown in Table 1 are added into a mixer and dry-mixed for 2 minutes to make them preliminarily mixed and uniform. Then, the dispersed polyaniline fiber and basalt fiber are added and stirred for 4 minutes at a stirring rate of 220-300 rpm (to avoid the fibers being broken due to excessive stirring speed). Finally, water and the admixtures shown in Table 1 are added, and the admixtures are first dissolved in water and stirred for 5 minutes until the concrete mixture reaches a uniform state, thereby obtaining fiber concrete.

[0069] When weighing, since polyaniline fibers are light and easily agglomerated due to electrostatic adsorption, it is best to use an electronic balance with high precision. Some dispersants can also be appropriately added to the fibers to facilitate subsequent dispersion. For example, a small amount of surfactant can be used as a dispersant and pre-mixed with the polyaniline fibers.

[0070] For basalt fiber, the equipment used to weigh basalt fiber should have sufficient accuracy. It is generally recommended to use an electronic scale with an accuracy of ±0.1% to weigh the fiber. Because the fiber has a certain degree of water absorption, if the ambient humidity is high, the fiber is easily affected by moisture. After being affected by moisture, the basalt fiber may clump, and its performance may also be affected, such as reduced strength. It is generally recommended to store the fiber in an environment with a relative humidity of less than 70%, for example, it can be placed in a warehouse with dehumidification equipment.

[0071] 2. Forming stage

[0072] The mixed fiber concrete can be molded according to different engineering requirements. If you are making concrete test blocks for mechanical properties testing, pour the concrete into the mold and vibrate it with a vibrator to make it dense. When vibrating, be careful to avoid excessive vibration that may cause concrete segregation, and also ensure that there are no obvious gaps inside the concrete. The vibration time can be determined based on factors such as the size of the test block and the fluidity of the concrete, generally between 10-30 seconds. If it is used for on-site pouring, such as pouring concrete pavements, bridges or building foundations, it is necessary to pour and vibrate in accordance with the corresponding construction specifications to ensure the density and surface flatness of the concrete.

[0073] 3. Maintenance stage

[0074] After forming, fiber concrete needs to be cured to ensure the normal hydration of cement and the development of concrete performance. At room temperature, it can be cured by covering with plastic film and wet cloth to prevent the water on the concrete surface from evaporating too quickly. The curing time is generally not less than 7 days. For some special environments or situations with higher durability requirements, the curing time can be extended to 14 days or longer. During the curing period, it is necessary to keep the concrete surface moist and avoid the concrete from being affected by adverse factors such as impact and vibration.

[0075] Comparative Example 1

[0076] The basalt fiber and polyaniline fiber in Table 1 were not added, and the other components were the same as those in Example 1.

[0077] Comparative Example 2

[0078] The basalt fiber in Table 1 was not added, and the other components were the same as those in Example 1.

[0079] Comparative Example 3

[0080] The polyaniline fiber in Table 1 was not added, and the other components were the same as those in Example 1.

[0081] Comparative Example 4

[0082] The polyaniline fiber and silica fume in Table 1 were not added, and the other components were the same as those in Example 1.

[0083] Table 1 Raw material ratio of fiber concrete

[0084]

[0085] Comparative Example 5

[0086] Fiber type screening: Various fibers were tested, such as polypropylene fiber and carbon fiber. Based on the addition of 1 kg of fiber per cubic meter of ordinary concrete, the dispersion of different fibers in concrete (observed by microscope to see how evenly the fibers are distributed in the concrete paste, divided into 5 levels, with 5 being the most even), the adhesion to the cement matrix (tested by a pull-out test, in N), and the improvement of concrete crack resistance (measured by the crack width of the circular constraint test, in mm) and mechanical properties (compressive strength, in MPa) were compared. The experimental data are shown in Table 2:

[0087] Table 2 Performance test results of concrete with different fiber types

[0088] Fiber Type Dispersion grade Adhesion force(N) Crack width(mm) Compressive strength(MPa) Polypropylene fiber 3 85 0.35 40 Carbon Fiber 2 145 0.2 48 Polyaniline fiber 4 125 0.25 45 Basalt fiber 4 135 0.23 46

[0089] The experiment found that although polypropylene fiber is cheap, it has low strength; carbon fiber has high strength, but poor dispersion and high cost. Polyaniline fiber and basalt fiber achieve a good balance between dispersion, strength and cost, and are suitable for anti-cracking fiber concrete.

[0090] Performance Testing

[0091] The fiber concrete prepared above was molded and cured, and then the following performance tests were performed:

[0092] 1. Compressive strength test: A standard cubic specimen with a size of 150mm×150mm×150mm was made and cured for 28 days under standard curing conditions (temperature 20±2℃, relative humidity ≥95%), and a compressive strength test was performed using a pressure testing machine.

[0093] 2. Bending strength test: a standard prism specimen with a size of 150 mm × 150 mm × 550 mm was made and cured for 28 days under standard curing conditions. The bending strength test was carried out using the three-point loading method.

[0094] 3. Tensile strength test: The tensile strength of concrete is determined by direct tensile test. The CMT5105 microcomputer-controlled electronic universal testing machine is used to conduct direct tensile test and stretch the standard specimen.

[0095] 4. Crack resistance test: The flat plate constraint method is used to test the crack resistance. Constraints are imposed on the surface of the specimen, and a layer of restraint device consisting of a steel mesh with a diameter of 6mm and a spacing of 100mm is embedded at the bottom. The distance between the steel mesh and the bottom of the specimen is 20mm. The constraint conditions of concrete in actual engineering are simulated, and the crack resistance is evaluated by observing the time when cracks appear and the width of cracks.

[0096] 5. Toughness test: The impact test method is adopted, and the standard specimen is impacted by a pendulum impact tester, and the energy absorbed when the specimen is destroyed is recorded to evaluate the toughness of the concrete. The test results of different concrete properties are shown in Table 3 below:

[0097] Table 3 Test results of different concrete properties prepared

[0098]

[0099]

[0100] Result analysis:

[0101] 1. Basalt fiber and polyaniline fiber form a three-dimensional network structure in concrete. When concrete is subjected to external force, the fiber can effectively disperse the stress and bear part of the load, thereby reducing the stress concentration inside the concrete matrix. There is a certain bonding force between the fiber and the concrete matrix, which enables the fiber to work with the concrete and enhance the overall performance of the concrete. When microcracks appear in the concrete, the fiber can prevent the cracks from further expanding through the interfacial bonding force, play a bridging role, and improve the crack resistance of the concrete.

[0102] 2. Basalt fiber and polyaniline fiber have different performance characteristics, and they work together in concrete to achieve better results. Basalt fiber has high strength and modulus, and can provide good mechanical support; polyaniline fiber has certain conductivity and chemical stability, which helps to improve the durability and corrosion resistance of concrete. The combination of the two can improve the mechanical properties of concrete while enhancing its durability and crack resistance.

[0103] It should be noted that the specific features, structures, materials or characteristics described in this specification may be combined in any one or more embodiments in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments and features of the different embodiments described in this specification without contradiction.

Claims

1. A fiber concrete, characterized in that: The raw material components include, by weight: 400-500 parts of cement, 750-1800 parts of aggregate, 4-8 parts of polyaniline fiber, 10-25 parts of basalt fiber and 140-180 parts of water.

2. The fiber concrete according to claim 1, characterized in that: The raw material components include, by weight: 450 parts of cement, 1650 parts of aggregate, 6 parts of polyaniline fiber, 15 parts of basalt fiber and 160 parts of water.

3. The fiber concrete according to claim 1 or 2, characterized in that: At least one of the following is met: The cement is Portland cement; The aggregate is at least one of coarse aggregate or fine aggregate; The polyaniline fiber has a length of 8-12 mm and a diameter of 20-30 μm; The basalt fiber has a length of 6-10 mm and a diameter of 10-15 μm.

4. The fiber concrete according to claim 3, characterized in that: At least one of the following is met: The cement is P·II type silicate cement; The coarse aggregate is granite crushed stone with a particle size of 5-25 mm and continuous grading; The fine aggregate is river sand or machine-made sand; The coarse aggregate is 900 parts, and the fine aggregate is 750 parts.

5. The fiber concrete according to any one of claims 1 to 4, characterized in that: The fiber concrete also includes raw material components of 0.5 to 60 parts of admixtures and 30 to 110 parts of mineral admixtures by weight.

6. The fiber concrete according to claim 5, characterized in that: The admixture includes at least one of a high-efficiency water reducing agent, a waterproofing agent, a retarder or an expansion agent.

7. The fiber concrete according to claim 6, characterized in that: At least one of the following is met: The high-efficiency water reducer is a polycarboxylic acid-based high-efficiency water reducer; The waterproofing agent is a cement-based penetrating crystalline waterproofing agent; The retarder is a hydroxycarboxylic acid and its salt retarder; The expansion agent is a calcium sulphoaluminate expansion agent; Preferably, the admixture includes 15 parts of polycarboxylic acid-based high-efficiency water reducing agent, 8 parts of cement-based penetrating crystalline waterproofing agent, 0.6 parts of hydroxycarboxylic acid and its salt retarder and 30 parts of calcium sulfoaluminate expansion agent.

8. The fiber concrete according to any one of claims 5 to 7, characterized in that: The mineral admixture is selected from at least one of fly ash and silica fume; preferably, the mineral admixture includes 70 parts of fly ash and 30 parts of silica fume.

9. The method for preparing fiber concrete according to any one of claims 1 to 8, characterized in that: The following steps are involved: First, dry-mix cement and aggregate evenly, then add polyaniline fiber and basalt fiber, continue stirring, and finally add water and stir evenly to obtain fiber concrete.

10. The method for preparing fiber concrete according to claim 9, characterized in that: First, dry-mix cement, aggregate and mineral admixtures evenly, then add polyaniline fiber and basalt fiber, continue stirring, and finally add water and admixtures and stir evenly to obtain fiber concrete.

Citation Information

Patent Citations

  • Liquid crystal polymer, fiber, preparation method of fiber and fiber concrete

    CN117024719A

Cited By

  • Multifunctional basalt fiber composite material and preparation method thereof

    CN121447938A